“It Can Be Magic:” Creating Age Awareness Through Contemporary Dance - Markula, Pirkko; Metzger, Kathy; Bliss, Tamara; Gervais, Wendy; Rintoul, Mary Ann; Vandkerkhove, Jodie (Frontiers in Sports and Active Living, 2022)
Professional dancers typically retire before age 40. Although the physical requirements for dance performance are often considered the reason for retirement, there is an increasing number dance researchers who demonstrate that the idealization of youthfulness on the stage is also a result of complex cultural, social, and economic realities and as such, in need of critique. As a group of mature women dancers who continue to perform, we aim to critique the idealization of youthfulness as a form of ageism in professional dance. In this paper, we present findings from our feminist memory-work study in which we critically reflected the rehearsals and performance of a choreography titled “Initiation.” We detail three main themes—”It Will Only Get Worse;” “It Can Be Magic;” “Once a Dancer Always a Dancer”—that emerged from our study. We conclude that we gained critical awareness of the gendered and ageist construction of dance as a performing art. As a result, we now feel empowered to continue our work as mature dance artists.